The Practice of Case Teaching Method in the Teaching of “Fire Investigation” - Wang, Xinyu; Zeng, Xiao; Li, Nan; Xing, Yue (Transactions on Social Science, Education and Humanities Research, 2023)
Fire investigation is a comprehensive applied discipline that studies fire traces, analyzes fire evidence, and deals with fire accidents. The case teaching method is conducive to integration of theory and practice, promoting the innovation of talent training mode, improving the comprehensive ability of students, and promoting the mutual benefit teaching. Combined with the training objectives, this paper firstly analyzes the necessity of the application of case teaching method in the teaching of Fire Investigation from three aspects: curriculum system construction, student literacy improvement, and teacher ability improvement. Secondly, it introduces the application practice process from three stages: pre class, in class, and post class. Finally, it proposes precautions from three aspects: case library construction, classroom design, and course evaluation.